2016
DOI: 10.1111/clr.12762
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a collagen membrane positioned between augmentation material and the sinus mucosa in the elevation of the maxillary sinus floor. An experimental study in sheep

Abstract: The application of a collagen membrane subjacent to the Schneiderian mucosa in a sinus floor elevation procedure did not influence the healing outcomes at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 25 publications
(51 reference statements)
9
31
0
Order By: Relevance
“…In fact, in the present study, the healing of the augmented sinus was also achieved in the group that used cortical lamina so that the partial exclusion of the sinus mucosa from the healing bone process seems not to have affected the results. This outcome is in agreement with the results from other reports on the healing in augmented sinus in sheep and rabbits in which the sinus mucosa was excluded from the elevated space by the use of collagen membranes [28,29,30]. …”
Section: Discussionsupporting
confidence: 92%
“…In fact, in the present study, the healing of the augmented sinus was also achieved in the group that used cortical lamina so that the partial exclusion of the sinus mucosa from the healing bone process seems not to have affected the results. This outcome is in agreement with the results from other reports on the healing in augmented sinus in sheep and rabbits in which the sinus mucosa was excluded from the elevated space by the use of collagen membranes [28,29,30]. …”
Section: Discussionsupporting
confidence: 92%
“…This study confirmed that membrane presents some osteogenic potential but its effective role in sinus floor elevation is much weaker than that of the surrounding bone walls. Furthermore, a recent animal study investigating the influence of a resorbable barrier membrane placed subjacent to a pristine sinus mucosa on the healing outcome of a sinus floor elevation procedure showed that Schneiderian membrane isolation from the regeneration area did not influence the healing outcomes at all (Scala et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on preclinical studies investigating the role of a collagen membrane placed on the perforation as well as on a schneiderian membrane without a perforation, no potential benefit due to the placement of a collagen membrane was demonstrated (Favero et al, ; Iida et al, ; Scala et al, ). A relatively small perforation (4 × 5 mm) might, however, act as a confounding factor (Favero et al, ).…”
Section: Discussionmentioning
confidence: 99%